CUSTOMER PREFERENCES ON SUSTAINABLE FASHION PURCHASES: A CONCEPTUAL MODEL - Florencia Devina Delimarta; Raden Aswin Rahadi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This research purpose is to investigate customer motivation when purchasing sustainable fashion. These research objectives are to investigate customers’ perception toward sustainable fashion, to determine the preferences of customers in buying sustainable fashion, and the range of price limits of customers in purchasing sustainable fashion. Therefore, for this research, there are several papers that are being reviewed and preliminary research being conducted. The literature analysis and preliminary studies have shown that customer preferences such as Price, Quality, Design, Brand Image, and Promotion influencing sustainable fashion purchases. Based on the literature review and preliminary study, this research was able to produce a simple conceptual framework. This researchâ€™ findings will be useful for fashion brand owners in developing their business. These findings can be useful to create pricing strategies, marketing strategies, and product strategies.